Case report: a rare initial presentation of gastrointestinal symptoms in systemic Lupus Erythematosus - Abdul Hadi, Azwanis; Abd Latip, Nurul Akmal; Ismail, Mohd Nizamuddin (IIUM Press, 2022)
Initial clinical presentation of Systemic Lupus Erythematosus (SLE) is varied as it affects various organs in the body. While typical presentation of SLE are cutaneous signs and joint pain, gastrointestinal (GI) manifestation is a rare initial presentation of SLE. We discuss the case of a 13-year-old girl who was diagnosed with SLE after she presented with symptoms similar to acute gastroenteritis. She presented with diarrhoea, vomiting, abdominal pain and bilateral ankle oedema; and was treated as acute gastroenteritis. She returned after one week with worsening symptoms. Her full blood count showed bicytopenia; her urinalysis had proteinuria and haematuria; and her renal profile revealed acute on chronic kidney injury which triggered suspicions of a more serious disease rather than simple viral gastroenteritis. Further investigations of positive anti-nuclear antibody, low complements and positive Coombs’s test supported the diagnosis of SLE. The diagnosis of SLE was confirmed when her renal biopsy reported crescentic lupus nephritis ISN/RPS Class 4. Additional investigation to investigate the cause of her gastrointestinal symptoms included an ultrasound abdomen which showed minimal ascites and bilateral renal parenchymal disease. She was planned for colonoscopy but due to the unavailability of paediatric endoscopy, endoscopy referral to a tertiary centre was postponed. However, her symptoms markedly improved with intravenous Cyclophosphamide which supported the diagnosis of GI SLE. This case report is to highlight that a patient with symptoms of simple viral gastroenteritis might have a more serious underlying disease. Full examination is important to elicit other signs which does not fit with typical viral gastroenteritis such as anemia and ankle oedema in this case. Safety netting and follow-up is a good practice to detect worsening symptoms earlier and to initiate further investigations. Lastly, though rare, SLE can present with gastroenteritis symptoms and is one of the differential diagnoses that should be considered.